Sistem Monitoring Helpdesk & Ticketing Dalam Penanganan Keluhan Perangkat Kerja Berbasis Web - Iwan Kurniawan; Munawaroh Munawaroh (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2022)
PT Lingkar Sembilan Titian Media is one of the companies engaged in creative industry technology. This company has several services, namely Web-Based & Mobile App Development, Digital Marketing & Campaign, Manage Service Provider, and Media & Broadcasting. The work that cannot be separated from technology causes frequent problems that require the IT Helpdesk division to solve. However, currently, complaints are still being made manually, there is not even a ticket number given by the IT Helpdesk to the user. So users can only wait for confirmation via Whatsapp or the Slack application. Not only that, the recording system for disturbances/damages experienced by users is still done manually and is not integrated, which makes it difficult for the Manager to monitor IT Helpdesk activities in real-time. Thus the company needs a system that can assist, manage, record & provide ticket numbers that can be accessed easily and together at PT Lingkar Sembilan Titian Media.This research aims to build a monitoring system that can make it easier for managers to monitor the work of the IT Helpdesk and Ticketing divisions that make it easier for employees to complain about work equipment issues. This research uses the waterfall method, while the analysis is carried out by conducting observations and interviews with related parties. The process design method is focused on model development using UML (Unified Model Language) and using the PHP programming language with the Code Igniter 3.0 framework and wampp v3.2.6 with Apache as the webserver and MySQL as database storage. The results of this study are in the form of a monitoring system for the IT helpdesk division and ticketing of complaints about work equipment at PT Lingkar Sembilan Titian Media. Keyword: Monitoring System, Helpdesk, Ticketing, Waterfall Methode